Analisis Kinerja Kolektor Distilasi Surya Kaca Ganda Dengan Heat Absorber - Jamal Jamal (Jurnal Teknik Mesin Sinergi, 2021)
Solar distillation is a water distillation technology to get fresh water from sea water by evaporating sea water by heating it with solar energy, which then condenses the water vapor to get fresh water. The use of heat absorbers is to increase the absorption of solar energy and lift water to the surface of the heat absorber material to be evaporated. This research was conducted to determine the effect of using various heat absorbers (charcoal, pumice and white sand) on the quantity of fresh water produced by a double glass solar distillatory and to determine the performance of a double glass solar distillation collector with various heat absorbers. This research was carried out by direct observation for data collection, direct testing was carried out on a double glass distillatory with various heat absorbers, for accuracy the research was carried out simultaneously for all types of heat absorbers in the alternative energy laboratory of the Department of Mechanical Engineering at the State Polytechnic of Ujung Pandang for 5 days. The test was carried out from 08.00 WITA to 17.00 WITA by recording data every 30 minutes. Based on the research and data analysis conducted, the average condensate volume for charcoal heat absorber is 157 ml, pumice stone is 141 ml and white sand is 80.8 ml. % and white sand 3,784%.